Perancangan Corporate Identity Sebagai Media Promosi Pada UMKM Fajar Mebel Berbasis Adobe Photoshop Adobe Premiere Pro Dan Coreldraw - Alwi Kurniawan; Diana Suksesiwaty Lubis (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study is to design a corporate identity for Fajar FurnitureUMKM and also as a tool for media promotion in order to introduce the company's productsto the wider community so that can be seen anywhere. The research method used is escriptivequalitative method, the design of corporate identity that can be visualized, one of which is alogo and the logo can later be applied to various promotional media, such as: businesscards, brochures, and others. And the existence of a video profile from the company aims topromote and introduce Fajar Furniture UMKM to the wider community. The results of thisresearch that has made a corporate identity in SMEs Dawn Furniture, so his guess peopleeasily find information about SMEs Dawn Furniture, Corporate Identity can also assist in thepromotion of the products are sold both from home or company.